1979
DOI: 10.1111/j.1600-0528.1979.tb01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high caries risk children using prevalence of filled surfaces as predictor variable for incidence

Abstract: The purpose of the present study was to determine the validity of prevalence of filled surfaces at 9 years of age as a screening criterion for prediction of future caries incidence. Retrospective data were available for 114 children who had participated in an incremental dental care program from 7 to 16 years of age. There was a significant positive correlation between prevalence of filled surfaces (FS) at age 9 and increment of surfaces filled during the subsequent 7 years. Thus only 13% of the variation in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Correlation coefficients of 0.3-0,4 have been reported between caries experience io the pritnary dentition and permanent teeth in the mixed dentition, especially the first molars (1^). Similar (5) or lower (1) conrelations have been found between caries experience in the permanent teeth of the early tnixed and caries increment in the completed pertnanent dentition. However, the association has not been investigated after both the pritnary and permanent teeth have been exposed to a potential caries risk for several years.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Correlation coefficients of 0.3-0,4 have been reported between caries experience io the pritnary dentition and permanent teeth in the mixed dentition, especially the first molars (1^). Similar (5) or lower (1) conrelations have been found between caries experience in the permanent teeth of the early tnixed and caries increment in the completed pertnanent dentition. However, the association has not been investigated after both the pritnary and permanent teeth have been exposed to a potential caries risk for several years.…”
supporting
confidence: 60%
“…However, the correlation between caries experience of the permanent teeth at 8 yr, i.e. caries of first molars, and caries increment from 8 to 16 yr was considerably lower, r= O.I7-0.32, atid also somewhat lower than the 0.36 between 9 and 16' yr reported earlier (5).…”
Section: Resultsmentioning
confidence: 51%
“…During the 1970s it became evident that the variation in caries progression persisted even though the prevalence of dental caries decreased. This phenomenon was in general termed polarization, in the sense that a group of children, most often termed the 'risk group', was in need of extensive operative treatment compared with the rest of the children (17)(18)(19)(20)(21)(22). Even though such observations have contributed to a change in the clinical work from being entirely non-specific towards more differentiation, the concept of grouping according to standardized procedures for examinations and for preventive measures still exists.…”
Section: Discussionmentioning
confidence: 99%
“…tive programs for patients at risk of caries and longer intervals between check-ups for non-risk individuals would be desirable from cost-benefit reasons. A number of different tests like caries prevalence, caries experience, oral hygiene level, rate of plaque formation, diet, buffer capacity of saliva, and the numbers oi Strep, mutans and lactobacilli in saliva have been developed for identification of individuals at risk of caries (4)(5)(6)(7)(8)(9)(10)(11)(12). Some of these tests are, however, time-consuming or are rarely available in the general dental clinic.…”
mentioning
confidence: 99%
“…Several studies have shown some relationship between past caries experience and future caries incidence (6,(13)(14)(15)(16)(17)(18). A number of studies address the relationship between caries experience of the primary dentition and the early permanent dentition.…”
mentioning
confidence: 99%